Efficacy of an imagery intervention to increase flow and performance in tennis competition - Koehn, S.; Morris, T.; Watt, A. P. (Medicine and Science in Tennis, 2006)
Imagery is one of the most powerful tools for sport psychological interventions to change cognitions and to increase performance (1). Flow is an optimal psychological state that facilitates superior performances (2). The purpose of this study was to investigate the efficacy of an imagery intervention to enhance flow and performance. In this single-case study, we followed an advanced junior tennis player over the course of eleven tennis competition matches. After having assessed a stable baseline trend, we introduced the intervention in the form of a tennis specific imagery script. Results revealed that flow and performance increased from baseline to post-intervention phase, and that performance was more stable throughout the post-intervention phase.